The transdiagnostic relationship of cumulative lifetime stress with memory, the hippocampus, and personality psychopathology. (November 2022) - Carcone, Dean; Gardhouse, Katherine; Goghari, Vina M.; Lee, Andy C.H.; Ruocco, Anthony C.
Abstract: Stress has a detrimental impact on memory, the hippocampus, and psychological health. Psychopathology research on stress has centered mainly on psychiatric diagnoses rather than symptom dimensions, and less attention has been given to the neurobiological factors through which stress might be translated into psychopathology. The present work investigates the transdiagnostic relationship of cumulative stress with episodic memory and the hippocampus (both structure and function) and explores the extent to which stress mediates the relationship between personality psychopathology and hippocampal size and activation. Cumulative lifetime stress was assessed in a sample of females recruited to vary in stress exposure and severity of personality psychopathology. Fifty-six participants completed subjective and objective tests of episodic memory, a T2-weighted high-resolution magnetic resonance imaging (MRI) scan of the medial-temporal lobe, and functional MRI (fMRI) scanning during a learning and recognition memory task. Higher cumulative stress was significantly related to memory complaints (but not episodic memory performance), lower bilateral hippocampal volume, and greater encoding-related hippocampal activation during the presentation of novel stimuli. Furthermore, cumulative stress significantly mediated the relationship between personality psychopathology and both hippocampal volume and activation, whereas alternative mediation models were not supported. The findings suggest that structural and functional activation differences in the hippocampus observed in case-control studies of psychiatric diagnoses may share cumulative stress as a common factor, which may mediate broadly reported relationships between psychopathology and hippocampal structure and function.